(untitled) (Global Journal of Human-Social Science, 2025)
The current study is related to the nature of land acquisition for new coal mining industrial establishments and resettlement occurring in different regions of West Bengal India as highly diverse regional socioeconomic issues The study finds the source of challenges to public laws and institutions providing humanitarian assistance as well as a matter of deep concern for human rights This study also finds various dimensions of bulk land acquisition cases in West Bengal and problems associated with it Thus the land acquisition due to coal mining and establishment of new industry is increasingly becoming a coercive operation lacking in sensitivity to human consequences involved in trail if devastation and trauma it leaves behind The piece of work probes into the deep land acquisition policy of the state government and people s reaction on land acquisition for establishment of new industry as well as extension of existing industry The findings focus on various dimensions of bulk land acquisition cases in West Bengal and problems associated with it